Problems of the complex regulation of the legal public procurement - Якимчук, Наталія Яківна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The theoretical and practical issues of public procurement relation regulating, systemic factors which cause infringementof the law in this field, as well as tasks and directions of its complex legal regulation are analyzed in the article.